Managing Community Forest Resources: Dynamics of Property Rights and Institutional Effectiveness in Nambo District - Yatim, Hertasning; Pakanyamong, Ambo Abd. Kadir; Yatim, Herwin; Zaman, Nur (Universitas Gadjah Mada, 2025)
In order to effectively achieve the objectives of local collective action, institutions must establish guidelines that align with community norms and are supported by organizational incentives and sanctions. This study aims to examine the dynamics of property rights over forest resources and the efficiency of local institutions in managing the Nambo Community Forest (HKm) within the Toili Baturube Model Production Forest Management Unit. Employing a qualitative case study approach, data collection methods include document analysis, in-depth interviews, and observations. The findings reveal that the forest status in Nambo District shifted to state ownership post-HKm policy implementation and Law 23 of 2014, leading to changes in community access rights. Additionally, community forest management is facilitated through collaboratively developed policies and agreements evaluated using the Ostrom principle design. The study underscores the importance of comprehensive strategies involving cooperation among regional authorities, local communities, and stakeholders to effectively manage shared resources like community forests. Strengthening institutional capacity, empowering local communities, and fostering collective action can enhance the sustainability and success of shared resource management initiatives.